Soluble γ-Secretase Modulators Selectively Inhibit the Production of the 42-Amino Acid Amyloid β Peptide Variant and Augment the Production of Multiple Carboxy-Truncated Amyloid β Species - Wagner, Steven L. (American Chemical Society, 2014)
[Image: see text] Alzheimer’s disease (AD) is characterized pathologically by an abundance of extracellular neuritic plaques composed primarily of the 42-amino acid amyloid β peptide variant (Aβ42). In the majority of familial AD (FAD) cases, e.g., those harboring mutations in presenilin 1 (PS1), there is a relative increase in the levels of Aβ42 compared to the levels of Aβ40. We previously reported the characterization of a series of aminothiazole-bridged aromates termed aryl aminothiazole γ-secretase modulators or AGSMs [Kounnas, M. Z., et al. (2010) Neuron 67, 769–780] and showed their potential for use in the treatment of FAD [Wagner, S. L., et al. (2012) Arch. Neurol. 69, 1255–1258]. Here we describe a series of GSMs with physicochemical properties improved compared to those of AGSMs. Specific heterocycle replacements of the phenyl rings in AGSMs provided potent molecules with improved aqueous solubilities. A number of these soluble γ-secretase modulators (SGSMs) potently lowered Aβ42 levels without inhibiting proteolysis of Notch or causing accumulation of amyloid precursor protein carboxy-terminal fragments, even at concentrations approximately 1000-fold greater than their IC(50) values for reducing Aβ42 levels. The effects of one potent SGSM on Aβ peptide production were verified by matrix-assisted laser desorption ionization time-of-flight mass spectrometry, showing enhanced production of a number of carboxy-truncated Aβ species. This SGSM also inhibited Aβ42 peptide production in a highly purified reconstituted γ-secretase in vitro assay system and retained the ability to modulate γ-secretase-mediated proteolysis in a stably transfected cell culture model overexpressing a human PS1 mutation validating the potential for use in FAD.